Konzepte sprachlicher Bildung im Fachunterricht – Gemeinsamkeiten und Unterschiede - Böttger, Lydia; Mischendahl, Anne; Niederhaus, Constanze (Mehrsprachigkeit in der Schule: Sprachbildung im und durch Sachunterricht)

ABIS 2024 – 28th International Workshop on Personalization and Recommendation - Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam; Herder, Eelco; Stojko, Laura; Strecker, Jannis (Proceedings of the Mensch & Computer (2024))

Augmented Reality-Assisted Multi-Robot Programming with Collision Warning - Mazur, Janet; Yigitbas, Enes (Proceedings of the 28th International Workshop on Personalization and Recommendation)

Projektmanagement Und Vorgehensmodelle 2024 – Neues Arbeiten in Projekten – Teamarbeit neu interpretiert - Fazal-Baqaie, Masud; Linssen, Oliver; Volland, Alexander; Yigitbas, Enes; Engstler, Martin; Bertram, Martin; Hanser, Eckhart

Education for democracy: the promotion of societal-democratic values, knowledge and participation in higher education quality assurance - Mauermeister, Sylvi; Maas, Cecilia (Beiträge zur Hochschulforschung)
If over the last two decades, the development of teaching and learning in higher education institutions has focused on employability and academic qualifications, the importance of a third function of higher education is being increasingly emphasised at European level: the promotion of societal-democratic engagement. In a qualitative analysis, we examine the importance that higher education institutions in Germany attach to the development of societal-democratic engagement in the context of their quality assurance processes. The results show that societal-democratic engagement as a dimension of quality is rather weakly embedded at both universities and universities of applied sciences. Considering the contemporary challenges to democracy worldwide, the results indicate that further attention to the development of societal democratic engagement within the context of quality assurance processes is certainly merited.

Evaluieren und Publizieren? - Sylvi, Mauermeister; Julia, Brose; Bettina, Langfeldt; Isabel, Steinhardt; Nicolai, Götze

Microscopic simulations of the dynamics of excitonic many-body correlations coupled to quantum light - Rose, Hendrik; Sharapova, Polina R.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVIII)

Perspektiven auf widerständisches Argumentieren im ‚Dritten Reich‘ - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik)
Resistance in the ‚Third Reich‘ was a mostly solitary and thus lonely struggle not only against the National Socialist regime, but also for being heard by the silent majority society. In addition to the various communicative practices of warning, admonishing, or calls to action, argumentation also played an important role. The task was not only to convince members of the majority society of the righteousness of their resistance goals and perspectives, but also to agree on goals and perspectives within the various resistance groups and in the exchange between these groups. This dual role of argumentation as a practice that is constitutive of both the group as well as the group’s identity makes this communicative practice an important phenomenon in capturing communicative conditions, circumstances, and paradigms of resistance to National Socialism. In this paper, these functional contexts are examined and the way in which arguments were used both to persuade members of the integrated society and to negotiate consensual principles and goals within resistance groups are discussed.

Stagings of Selfmarginalization, -stigmatization and -victimization in Martin Heidegger's Textual Communications. Reflecions on the Necessity of a Discourse-Linguistic as well as a Discourse-Ethical Re-Reading of Heidegger's Communicative Behaviour - Markewitz, Friedrich (Zeitschrift für Diskursforschung)

HenDi-Data (data package) v6.0.0 - Capelle, Irmlind; Ried, Dennis; Minetti, Elena; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Radikaler Digitaler Humanismus. Eine Philosophie für die digitale Gesellschaft des 21. Jahrhunderts. - Fuchs, Christian

Soziale Medien und Kritische Theorie. Eine Einführung. - Fuchs, Christian

HenDi-ODD - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v6.0.0 - Ried, Dennis

Felder der Nachhaltigkeits- und Wissenschaftskommunikation in der BBNE – Erkenntnisse der wissenschaftlichen Begleitung aus drei Transferprojekten - Kiepe, Karina; Pranger, Jan; Schlömer, Tobias; Reißland, Jens; Rüdebusch, Gerrit; Beer, Mareike (Berufsbildung für nachhaltige Entwicklung im Transfer. Verbreitung, Verstetigung und Transferforschung als Kern der Modellversuche 2020-2022)

Die Erkundung von Phänomenen und Schlüsselstellen des Transfers von Berufsbildung für eine Nachhaltige Entwicklung (BBNE) – eine Transfermodellierung - Schlömer, Tobias; Kiepe, Karina; Rüdebusch, Gerrit; Günther, Niklas; Liehr, Jennifer (Berufsbildung für nachhaltige Entwicklung im Transfer. Verbreitung, Verstetigung und Transferforschung als Kern der Modellversuche 2020-2022)

Aus- und Weiterbildungspersonal in Unternehmen. Gestalter:innen einer Berufsbildung für eine nachhaltige Entwicklung - Krause, Ina; Kiepe, Karina (Weiterbildung - Zeitschrift für Grundlagen, Praxis und Trends)

Betriebliche Weiterbildungsarbeit im Wandel unterstützen (Editorial) - Krause, Ina; Kiepe, Karina; Egger, Rudolf (Weiterbildung - Zeitschrift für Grundlagen, Praxis und Trends)

An efficient compact blazed grating antenna for optical phased arrays - Farheen, Henna; Joshi, Suraj; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Journal of Physics: Photonics)
Phased arrays are vital in communication systems and have received significant interest in the field of optoelectronics and photonics, enabling a wide range of applications such as LiDAR, holography, wireless communication, etc. In this work, we present a blazed grating antenna that is optimized to have upward radiation efficiency as high as 80% with a compact footprint of 3.5 μm × 2 μm at an operational wavelength of 1.55 μm. Our numerical investigations demonstrate that this antenna in a 64 × 64 phased array configuration is capable of producing desired far-field radiation patterns. Additionally, our antenna possesses a low side lobe level of -9.7 dB and a negligible reflection efficiency of under 1%, making it an attractive candidate for integrated optical phased arrays.
Keywords: tet_topic_opticalantenna

Siebter Oktober Dreiundzwanzig. Antizionismus und Identitätspolitik - Vukadinovic, Vojin Sasa (Siebter Oktober Dreiundzwanzig. Antizionismus und Identitätspolitik)